Induction of transgenerational toxicity is associated with the activated germline insulin signals in nematodes exposed to nanoplastic at predicted environmental concentrations - Liu, Huanliang; Zhao, Yunli; Hua, Xin; Wang, Dayong (Ecotoxicology and environmental safety, 2022)
Exposure to nanoplastics can induce toxicity on organisms at both parental generation (P0-G) and the offspring. However, the underlying mechanism remains unknown. Using Caenorhabditis elegans as a model organism, exposure to 20-nm polystyrene nanoparticle (PS-NP) (1-100 μg/L) upregulated the expressions of insulin ligands (INS-39, INS-3, and DAF-28), and this increase could be further detected in the offspring after PS-NP exposure. Germline ins-39, ins-3, and daf-28 RNAi induced resistance to transgenerational toxicity of PS-NP, indicating that increase in expression of these three insulin ligands mediated induction of transgenerational toxicity. These three insulin ligands transgenerationally activated function of insulin receptor DAF-2 to control transgenerational toxicity of PS-NP. Exposure to 1-100 μg/L PS-NP further upregulated DAF-2, AGE-1, and AKT-1 expressions and downregulated DAF-16 expression. During transgenerational toxicity control, DAF-16/AKT-1/AGE-1 was identified as downstream signaling cascade of DAF-2. Moreover, transcriptional factor DAF-16 activated two downstream targets of HSP-6 (a mitochondrial UPR marker) and SOD-3 (a mitochondrial SOD) to modulate transgenerational toxicity of PS-NP. Our findings indicate a crucial link between activation of insulin signaling and induction of transgenerational toxicity of nanoplastics at low concentrations in organisms.Exposure to nanoplastics can induce toxicity on organisms at both parental generation (P0-G) and the offspring. However, the underlying mechanism remains unknown. Using Caenorhabditis elegans as a model organism, exposure to 20-nm polystyrene nanoparticle (PS-NP) (1-100 μg/L) upregulated the expressions of insulin ligands (INS-39, INS-3, and DAF-28), and this increase could be further detected in the offspring after PS-NP exposure. Germline ins-39, ins-3, and daf-28 RNAi induced resistance to transgenerational toxicity of PS-NP, indicating that increase in expression of these three insulin ligands mediated induction of transgenerational toxicity. These three insulin ligands transgenerationally activated function of insulin receptor DAF-2 to control transgenerational toxicity of PS-NP. Exposure to 1-100 μg/L PS-NP further upregulated DAF-2, AGE-1, and AKT-1 expressions and downregulated DAF-16 expression. During transgenerational toxicity control, DAF-16/AKT-1/AGE-1 was identified as downstream signaling cascade of DAF-2. Moreover, transcriptional factor DAF-16 activated two downstream targets of HSP-6 (a mitochondrial UPR marker) and SOD-3 (a mitochondrial SOD) to modulate transgenerational toxicity of PS-NP. Our findings indicate a crucial link between activation of insulin signaling and induction of transgenerational toxicity of nanoplastics at low concentrations in organisms.